Cardiovascular Risk and Mineral Bone Disorder in Patients with Chronic Kidney Disease - Hagen Staude; Susann Jeske; Karin Schmitz; Gert Warncke; Dagmar-Christiane Fischer (Karger Publishers, 2013)
The term chronic kidney disease-mineral bone disorder has been coined recently to highlight that the disturbed mineral and bone metabolism is a major contributor to vascular calcification and finally cardiovascular disease. This syndrome is characterized by clinical, biochemical and/or histological findings, i.e. i) biochemical alterations in the homeostasis of calcium, phosphate and their key player parathyroid hormone (PTH), Fibroblast growth factor-23 (FGF-23), klotho and vitamin-D, ii) the occurrence of vascular and/or soft tissue calcification, and iii) an abnormal bone structure and/or turnover. Apart from the combined and synergistic action of "traditional" and uremia-related risk factors, promoters and inhibitors of calcification have to be considered as well. This review will focus on the disturbed mineral metabolism as the triggering force behind distortion of vascular integrity and cardiovascular malfunction in CKD patients.